Review of Economics and Statistics 2024 Annual Report - Board, Editorial (The Review of Economics and Statistics, 2024)
Current Editorial Board:Treb Allen, Dartmouth CollegePierre Azoulay, Massachusetts Institute of TechnologyWill Dobbie (Co-Chair), Harvard UniversityRaymond Fisman (Co-Chair), Boston UniversityBenjamin R. Handel, University of California, BerkeleyPeter Hull, Brown UniversityBrian A. Jacob, University of MichiganScott Kominers, Harvard UniversityTavneet Suri, Massachusetts Institute of TechnologyStephen Terry, University of MichiganRecently Retired from the Editorial Board:Olivier Coibion, University of Texas, AustinDaniel Xu, Duke UniversityTable 1—Manuscripts Submitted and PublishedThis table shows the trends in papers submitted and published over the past five years. The journal saw increased growth in submissions of papers from 2019 to 2020. Submission numbers remained steady from 2020 to 2021, declined by 10% in 2022, and then remained steady from 2022 to 2023. The number of published papers increased by 25 in 2022 and an additional 17 papers in 2023 due to the publication of larger issues.Table 2—Status of Manuscripts by Year of Submission, 2019–2023This table shows the status of manuscripts submitted over the past five years. The number of papers summarily rejected has remained steady, ranging from 54% to 61% of papers submitted. The percent of papers sent out for review but ultimately rejected has also remained steady, ranging from 30% to 35% of papers. Acceptance rates range from 2% to 11% of papers submitted. Papers submitted in 2023 have not had enough time to reflect the acceptance rate.Table 3—Decision Time for Manuscripts Sent to Referees for ReviewThis table reports the decision time for manuscripts sent to referees for review over the past five years. The average decision time for papers that were sent to referees has remained steady, ranging from 82 to 95 days.Table 4—Distribution of First Decision Times, by Submission YearThis table includes all first-round paper submissions and shows the distribution of decision times in monthly increments for the past five years. This table also reflects the improvement in the journal's decision turnaround times. In 2023, 82% of manuscripts received a decision within three months and 99% within six months.Table 5—Subject Matter of Published Manuscripts, 2023This table shows the distribution of subject matter of papers published in 2023. These papers covered a variety of subjects, but the most common published topics were microeconomics; mathematical and quantitative methods; and health, education, and welfare. Table 1.Manuscripts Submitted and Published, 2019–2023YearSubmittedPublished20191,3306620201,6666520211,6746520221,4809020231,445107